Faculty Members' Perceptions Towards E-Learning - Rona Fajar Wana (Journal of Language Education and Educational Technology (JLEET), 2022)
The aim of this study was to investigate faculty members' perceptions towards e-learning and to identify the most critical factor for using e-learning in the English and Indonesian language Departments at Halu Oleo University. A descriptive quantitative approach was used in this research to gain a comprehensive understanding of the topic. For this purpose, 40 lecturers were selected as the main focus of the study. Data was collected using a close-ended questionnaire with 25 items and analyzed using the SPSS 16.0 version. The results showed that faculty members' perceptions towards elearning were positive, with almost all lecturers tending to give positive responses in both aspects of perception towards the use of e-learning in teaching. E-learning was seen to help lecturers in all aspects of their teaching practice, improve student achievement in learning, and was also easy for them to use and apply in their teaching practice. Moreover, the dominant aspect of using e-learning in teaching practice was the Perceived Ease of Use (PEOU) aspect. An important factor to be considered based on participants' responses regarding elearning is the limitations of the internet or quotas for teachers or lecturers themselves. However, the results show that elearning is not limited by time, distance, or place. If faculty members do not have a good internet connection or their internet quota is insufficient, the learning process may not be carried out properly.